Assessment of MDEA absorption process for sequential H2S removal and CO2 capture in air-blown IGCC plants. (1st December 2016) - Moioli, Stefania; Giuffrida, Antonio; Romano, Matteo C.; Pellegrini, Laura A.; Lozza, Giovanni
Highlights: Air-blown IGCC plants with sequential H2 S removal and CO2 capture are investigated. Two MDEA-based processes are proposed for sequential H2 S removal and CO2 capture. The influence of a low- and a high-sulphur coal and of two combustion turbines is assessed. Net efficiencies between 36.6% and 40.4%, with 95% of CO2 capture, are achieved. Better IGCC performance is always achieved in case of low-sulphur coal gasification. Abstract: This work deals with pre-combustion CO2 capture by Methyldiethanolamine (MDEA) scrubbing in air-blown integrated gasification combined cycles (IGCCs). Two types of coal, with low- and high-sulphur content, are considered as fuel input in power plants, as well as two combustion turbines, with different turbine inlet temperature, representative of state-of-the-art and advanced technologies. The gasification section and the power island are simulated by means of the proprietary code GS. Acid gas removal (AGR), consisting in the sequential H2 S removal and CO2 capture from the syngas by MDEA solvent, is calculated with Aspen Plus®. MDEA concentration and solvent circulation are varied in each of the assessed cases to comply with the target CO2 capture efficiency and with the CO2 and H2 S purity specifications. The resulting heat duties for H2 S and CO2 stripping, the consumption of the auxiliaries in the AGR plants, as well as the CO2 compression work are used to calculate the energy and mass balances of the integrated gasification combined cycles. Sensitivity analysis on the temperature approach in the recuperative heat exchanger of the CO2 capture section and on the pressure of the CO2 stripping column have been performed to assess potential energy savings. Results are compared with benchmark IGCC plants without CO2 capture. Net electric efficiencies between 36.6% and 40.4%, with 95% of CO2 capture efficiency, are achieved depending on the coal quality (i.e. the sulphur content), the combustion turbine technology and the MDEA regeneration pressure and heat exchanger temperature difference. Correspondingly, a specific primary energy consumption for CO2 avoided (SPECCA) between 2.85 and 3.2  MJ / kg CO 2 for the low-sulphur coal cases and between 3.2 and 3.7  MJ / kg CO 2 for the high-sulphur coal cases have been calculated.